2021
DOI: 10.1002/ajp.23330
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pinworm (Trypanoxyuris) infection and gut bacteria in wild black howler monkeys (Alouatta pigra)

Abstract: Gut bacteria may coexist with other groups of organisms, such as nematode parasites, that inhabit the gastrointestinal tract of primates; however, the possible effects of endoparasites on bacterial communities are frequently overlooked. Here we explored whether infection with Trypanoxyuris, an oxyurid gastrointestinal parasite, is associated with changes in the gut bacterial community of wild black howler monkeys (Alouatta pigra), by comparing gut bacterial communities of consistently infected individuals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
(96 reference statements)
2
4
0
1
Order By: Relevance
“…Our results support previous reports from redfronted lemurs that detected seasonal differences in the abundances of Chromadorea , and protozoa diversity 73 . Parasite richness only explained very low variation in bacterial beta diversity but associated positively and also negatively with certain bacterial taxa, supporting other studies from non-human primates 28 30 . Positive associations with Succinivibrio and Verrucomicrobiota have been reported in humans as well 74 , 75 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results support previous reports from redfronted lemurs that detected seasonal differences in the abundances of Chromadorea , and protozoa diversity 73 . Parasite richness only explained very low variation in bacterial beta diversity but associated positively and also negatively with certain bacterial taxa, supporting other studies from non-human primates 28 30 . Positive associations with Succinivibrio and Verrucomicrobiota have been reported in humans as well 74 , 75 .…”
Section: Discussionsupporting
confidence: 88%
“…For instance, in non-human primates, higher bacterial alpha diversity correlates to higher eukaryotic diversity 27 . Therefore, the presence of helminths and/or protozoa may impact the abundances of bacterial taxa [28][29][30] . Despite being challenging, research on wild animals provide an exceptional possibility to apply metacommunity concepts for investigating the drivers of the gut microbiome in undisturbed scenarios 5,8 .…”
mentioning
confidence: 99%
“…Helminth infection has partially explained bacterial microbiome variation in wild lemurs, though findings were not consistent when the studied populations were analysed separately (de Winter et al, 2020). In wild black howler monkeys ( Alouatta pigra ), differences in the community composition of gut bacteria were weakly associated with pinworm ( Trypanoxyuris ) infection, a gastrointestinal helminth, though a better understanding of the parasite–microbiome interplay was called for (Martínez‐Mota et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It will also be important to explore the extent to which the magnitude of these effects varies across different host species and the physiological pathways that contribute to this variation. Although several populations of black howler monkeys inhabit highly disturbed tropical forests (Pozo-Montuy et al, 2011;Rangel-Negrín et al, 2014b;Klass et al, 2020;Martínez-Mota et al, 2021) and are most likely exposed to environmental stressors (Martínez-Mota et al, 2007;Behie and Pavelka, 2013;Rangel-Negrín et al, 2014a), these primates might have coping mechanisms to deal with food availability deficits resulting from forest loss and fragmentation. For instance, found that SCFA produced by gut bacteria of howler monkeys were increased during periods of low energy intake, which suggests that microbial metabolism may support energy availability under critical periods of low food intake.…”
Section: Discussionmentioning
confidence: 99%